2018
DOI: 10.1038/s41598-018-22824-6
|View full text |Cite
|
Sign up to set email alerts
|

Early- and Long-term Outcomes of Cardiovascular Surgery via Minimal Right Vertical Infra-axillary Thoracotomy: A 15-year Study of 1,126 Patients

Abstract: This study reviews our results and experience with cardiothoracic surgery via RVIAT over the past 15 years. This retrospective overview summarises our results, describing the early and late clinical outcomes of 1,126 patients, including 370 ASD closures, 488 VSD closures and 268 valve surgeries, at a single center between October 2001 and December 2015. The mean follow-up time was 52 ± 35 months (range 8–120 months). The mean incision length was 6 ± 2.22 cm (range 3.9–8.9 cm). No patient required conversion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Studies have shown that the right infra-axillary thoracotomy incision is mostly made vertically (28,29). We performed the thoracotomy skin incision parabolically to reduce skin necrosis due to tension caused by the thorax retractor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the right infra-axillary thoracotomy incision is mostly made vertically (28,29). We performed the thoracotomy skin incision parabolically to reduce skin necrosis due to tension caused by the thorax retractor.…”
Section: Discussionmentioning
confidence: 99%
“…The incision is in the chest wall, which has low muscle mass and is far from the costochondral junction; it does not interfere with the development of the chest wall, particularly in young patients. In addition, femoral cannulation is not necessary [Casselman 2007, Wang 2018, thus it also avoids femoral artery injury. Second, this incision offers excellent visualization of mitral valve structures in a direct-line view.…”
Section: Discussionmentioning
confidence: 99%
“…A right infra-axillary incision has been widely used in our center for cosmetic purposes in young people as a good alternative to standard median sternotomy [Wang 2018]. It was first used to repair atrial septal defect, partial atrioventricular septal defect, and ventricular septal defect.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial septal defects (ASDs) are treated surgically only when percutaneous techniques are technically not feasible because of large size or insufficient margins. The growing demand for minimally invasive and cosmetic approaches to surgery has contributed to development of many techniques that include right posterolateral thoracotomy, 2 inframammary anterior thoracotomy, 3 muscle-sparing horizontal, 4,5 or vertical axillary thoracotomy, 6,7 and mini/or subxiphoid sternotomy. 8,9 Of these techniques, axillary thoracotomy has significant advantages.…”
Section: Introductionmentioning
confidence: 99%